Recent Insights into Rate Performance Limitations of Li‐ion Batteries. Issue 2 (23rd November 2020) - Heubner, Christian; Nikolowski, Kristian; Reuber, Sebastian; Schneider, Michael; Wolter, Mareike; Michaelis, Alexander
Abstract: Increasing the fast charging capabilities and the driving range of electric vehicles are major goals in Li‐ion battery research to accelerate mass market adoption and reduce greenhouse gas emissions. This requires a fundamental understanding of the performance limiting factors to enable a knowledge‐based optimization of materials, electrode design and cell architectures. Herein, electrochemical fundamentals and recent insights concerning rate performance limitations of Li‐ion batteries at the electrode level are reviewed and discussed from charge and mass transport perspectives. The application of straightforward analytical and semi‐empirical models is highlighted in view of understanding specific performance limiting factors of electrodes for Li‐ion batteries based on experimental investigations. The summarized insights are discussed regarding promising improvement strategies to approach the practical limits of liquid electrolyte‐based Li‐ion batteries. Abstract : Room for improvement : Increasing the fast charging capabilities and the driving range of electric vehicles requires a fundamental understanding of the performance limiting factors to enable a knowledge‐based optimization of materials, electrode design, and cell architectures. This Review highlights recent insights concerning rate performance limitations of Li‐ion batteries at the electrode level and summarizes the most promising improvement strategies.